Hubungan Spiritualitas, Resiliency Of Self Efficacy Dan Dukungan Sosial Dengan Kesejahteraan Psikologis Subjektif Pada Penderita Hepatitis B - Vereswati, Hermiana, Dr. Nisa Rachmah N.A., M.Si, Psi (2014)
Indonesia endemic Hepatitis B, this prevalency about 9,3% from total population in Indonesia. Stigma and benefits of treatment have not been evaluated by government, this disease affects psychological, fisiological Hepatitis B patients. The aim of this study was to investigate the association between spirituality, resiliency of self efficacy and social support to subjective well being in Hepatitis B patients. The study included 30 participants with Hepatitis B (HBsAg) positive diagnosis without liver chronic complication, who were aged between 18 and 65 years old. Participants were recruited from hepatology outpatients hospitals and patients from clinic laboratory. The quantitative study with a purposive sampling method was utilized. Method of analysis data was used non parametric, kendall tau correlation. The findings of this study illustrate there was significant association between spirituality and subjective well being to Hepatitis B respondents. There was no association between resiliency of self efficacy and subjective well being to Hepatitis B respondents. There was association between social support and subjective well being to Hepatitis B respondents. The criterion satisfaction of life was highest. Criterion spirituality was higher, criterion resiliency of self efficacy and social support was highest. Generalization this research only for Hepatitis B population. The qualitative study can be use for further research to understand subjective well being Hepatitis B respondents. The study about resiliency of self efficacy is useful to increase subjective well being Hepatitis B respondents. Social culture, economic status, and personality traits was another factor could influence Hepatitis B behaviour to this research